Transitive Verbs and Causative Construction in Riau Melay Language, Pasir Pengaraian Dialect - Tambusai, Azhary; Nasution, Khairina (Universitas Syiah Kuala, 2025)
This study aims to analyze the forms, morphosyntactic features, and causative as well as applicative constructions in the Pasir Pengaraian dialect of Riau Malay. Employing a qualitative descriptive framework, data were collected through in-depth interviews and recordings of natural speech from native speakers in Pasir Pengaraian, Rokan Hulu, Riau. Data analysis was conducted using distributional method, involving the direct constituent analysis (BUL), deletion, and expansion techniques. The findings identify three categories of transitive verbs: monotransitive, ditransitive, and semitransitive, each with distinct argument configurations. Causative constructions in this dialect are classified into three typesanalytic, morphological, and lexical, each reflecting valency expansion through the addition of a causative agent.